PENERAPAN METODE PEMBELAJARAN DAHSYAT â€œPOWER TEACHINGâ€ - Suwirya, I Wayan; Astawa, I Nengah (Jurnal Santiaji Pendidikan (JSP), 2019)
This article will discuss the Power Teaching Learning method which is more recently known as the Whole Brain Teaching method, which has the same concept as Brain Based Teaching. Power Teaching, in Indonesian can be said "awesome learning"! While the phrase "whole brain teaching" - learning with the whole brain - implies that this learning optimizes the work of the brain of students, left brain, right brain, brain. In other languages, it might be said that this learning involves the aspects of students with 'high impact': cognitive, affective and psychomotor. How effective is this "whole-brain" learning? The writer has tried to apply this method in Public and Private Junior high schools Schools in Denpasar. The results are very encouraging and satisfactory to be able to increase the efficiency, effectiveness and learning outcomes of students. This method is a learning model that is able to focus students' attention on learning through varied activities by combining visual, verbal and kinesthetic aspects